Reassessment of small lymphocytic lymphoma in the era of monoclonal B-cell lymphocytosis - Sarah E. Gibson; Steven H. Swerdlow; Judith A. Ferry; Urvashi Surti; Paola Dal Cin; Nancy Lee Harris; Robert P. Hasserjian (Haematologica, 2011)
Background In the 2008 World Health Organization classification, small lymphocytic lymphoma is defined as a neoplasm with the tissue morphology and immunophenotype of chronic lymphocytic leukemia, but with absence of leukemia. Minimal criteria of tissue involvement to separate small lymphocytic lymphoma from monoclonal B-cell lymphocytosis have not been defined.Design and Methods We reviewed the clinicopathological features of 36 patients with extramedullary tissue biopsies containing chronic lymphocytic leukemia-type cells and less than 5×109/L peripheral blood monoclonal B cells. Pathological features (extent and patterns of involvement, architectural preservation, presence of proliferation centers) as well as cytogenetic and radiological findings were examined in relation to clinical outcome.Results The biopsies were performed to evaluate lymphadenopathy in 20 patients and for other reasons (most frequently staging of a non-hematologic neoplasm) in 16 patients. At latest follow-up (median 23 months), 21 untreated patients had no or stable lymphadenopathy, 3 had regressed lymphadenopathy, and 12 had developed progressive lymphadenopathy and/or received therapy for chronic lymphocytic leukemia/small lymphocytic lymphoma. Features associated with progression/treatment included lymph nodes 1.5 cm or greater on imaging studies (P=0.01) and presence of proliferation centers in the biopsied tissue (P=0.004). Neither the size nor extent of involvement of the excised lymph node correlated with progression/treatment.Conclusions Our findings suggest that biopsies containing chronic lymphocytic leukemia-type cells, but lacking proliferation centers and with non-enlarged or only slightly enlarged lymph nodes on imaging, represent a very indolent disease that may best be considered a tissue equivalent of monoclonal B-cell lymphocytosis rather than overt small lymphocytic lymphoma. We propose that such cases be designated as tissue involvement by chronic lymphocytic leukemia/small lymphocytic lymphoma-like cells of uncertain significance.